Practical big data analytics : hands-on techniques to implement enterprise analytics and machine learning using Hadoop, Spark, NoSQL and R - Dasgupta, Nataraj (Packt Publishing, 2018)
Big Data analytics relates to the strategies used by enterprises to process and analyze large amounts of data to bring out hidden insights. With the help of open source and enterprise tools, such as R, Python, Hadoop, and Spark, you will learn how to effectively mine your Big Data. By the end of this book, you will have a clear understanding ...